SEROEPIDEMIOLOGY AND RISK FACTORS OF HEPATITIS B VIRUS IN JIBLAH TOWN, YEMEN - Al-Mohani, Sadiq Kaid (Universal Journal of Pharmaceutical Research, 2023)
Aims and objective: Viral Hepatitis is a major global health problem affecting millions of people worldwide. The endemicity of hepatitis B virus infection believed high in Yemen. Data for prevalence of hepatitis B virus in Jiblah town in Yemen are rare and inadequate. Therefore, this study aimed to assess the seroprevalence of Hepatitis B virus and associated risk factors aming the general population of Jiblah town, Yemen. Methods: A total of 100 participated included in this study. Serum samples were collected and assayed for HBsAg using the ELISA quantitative technique. A structured questionnaire was used to collect behavioral and sociodemographic data. Results: the results revealed that, the seroprevalence of hepatitis B virus was 3.33%. There was statistically significant differences between hepatitis B virus infection and monthly income. Conclusion: The finding of this study indicated that the magnitude of hepatitis B virus infection among the general population was intermediate level. Modifiable risk factor, monthly income was identified. Peer Review History: Received: 8 February 2023; Revised: 13 March; Accepted: 27 April 2023, Available online: 15 May 2023 Academic Editor: Dr. Rola Jadallah , Arab American University, Palestine, rola@aauj.edu Reviewers: Prof. Hassan A.H. Al-Shamahy, Sana’a University, Yemen, shmahe@yemen.net.ye Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com